Ativismo e modernidade negra - Figueiredo, Angela (Afro-Ásia, 2022)
Resenha de; GUIMARÃES, Antonio Sérgio Alfredo. Modernidades negras: a formação racial brasileira (1930-1970). São Paulo: Editora 34, 2021. 295 p.